Kinematical characterisation of a basic head-out aquatic exercise during an incremental protocol - Oliveira, C.; Teixeira, G.; Costa, M. J.; Marinho, D. A.; Silva, A. J.; Barbosa, T. M. (Biomechanics and Medicine in Swimming XI, 2010)
The aim of this study was to analyze the relationships between musical cadence and kinematical characteristics of a basic head-out aquatic exercise, when immersed to the breast. Six young women with at least one year of experience conducting head-out aquatic classes were videotaped in the sagital plane with a pair of cameras providing a dual projection from both above and underwater performing 5 incremental bouts (120 b/min, 135 b/min, 150 b/min, 165 b/min and 180 b/min) of the basic head-out aquatic exercise "rocking horse". There was a decrease of the cycle period throughout the incremental protocol. Relationships between horizontal or vertical displacements with music cadence were not significant. On the other hand, increased cadence imposed increased segmental and centre of mass` velocities. As a conclusion expert and fit subjects seem to increase segmental velocity with increasing musical cadence to avoid the decrease of the segmental range of motion.